Obituary: Ian Dickson - Delyth Edwards (Scottish Journal of Residential Child Care)
Sometime in 2014, I was reading an article in The Big Issue that was discussing an announcement made on the 14th of December in 2013 by the government, that children who were living in foster care would be allowed and supported to remain with their foster carers until they were 21 years of age. This policy became known as ‘staying put’ and it infuriated me. What about young people growing up in children’s homes, how can they be so cruelly excluded from this, I thought to myself. I wanted to know more, and I wanted to see if anyone else was outraged by this plan and the hierarchy being created through it. With some online research I became aware of Every Child Leaving Care Matters (ECLCM), ‘a campaign group, without funding or political affiliations with any other group, formed to stop Government discrimination against children in residential care who want support to 21, the same as those in foster care’ (ECLCM). This group, made up of many care experienced people, shared my outrage and they were doing something about it, they were collecting signatures for a petition. I signed the petition, I followed the campaign on Twitter, and I also followed the founding members of this group, with Ian Dickson being one of them.